STUDY OF ARCHITECTURE IN BULGARIA DURING THE 19TH TO MID 20TH CENTURY (Innovation in Woodworking Industry and Engineering design, 2026)
In the article, the development of Bulgarian architecture from the Revival period to the mid-20th century is considered. An analysis is performed of existing historical patterns in the residential and public architecture. Their development is traced over the time. The research aims to show how eclectical European style of this period leaves a mark on Bulgarian architecture. The purpose of this study is to explain the variety of styles in interior and furniture, using basic architectural elements as a source.